Curcumin Entrapped Into Lipid Nanosystems Inhibits Neuroblastoma Cancer Cell Growth and Activates Hsp70 Protein - Bondì, M. L.; Craparo, E. F.; Picone, P.; Carlo, M. D.; Gesu, R. Di; Capuano, G.; Giammona, G. (Current Nanoscience, 2010)
Curcumin is a natural anti-cancer compound utilized on a wide variety of human cancer cell lines and animal carcinogenesis models. However, its clinical application has been limited for its minimal systemic bioavailability. Nanoparticle-based drug delivery approaches have the potential for rendering hydrophobic molecules such as curcumin dispersible in aqueous media, thus overtaking the limits of its poor solubility. In this paper, we reported the preparation and chemical-physical characterization of Nanostructured Lipid Carriers (NLC) containing curcumin, based on Imwitor, Compritol or Precirol as lipid matrix. By in vitro experiments, we have demonstrated that these nano-systems are able to carry curcumin into LAN5 neuroblastoma cells and their effect on cell mortality is higher than free curcumin. However, the best results were obtained when the NLC-c system was utilized. Moreover, we have demonstrated that curcumin activates Hsp70 protein and that this effect is enhanced when the same dose of curcumin is administered as drug-loaded NLC. The obtained results clearly suggest that these nanoparticles are a potential curcumin delivery systems and encourage, in future, for planning in vivo studies towards cancer and other diseases that might benefit from the curcumin effects.
Keywords: cancer